Torticollis as Presentation for Atypical Kawasaki Disease Complicated by Giant Coronary Artery Aneurysms - Tracey Dyer; Paul Dancey; John Martin; Suryakant Shah (Case Reports in Pediatrics)
Kawasaki disease (KD) is an acute systemic vasculitis of childhood. The diagnosis can be made in a patient who presents with a prolonged high fever and meeting at least four of five criteria including polymorphous rash, mucosal changes, extremity changes (including swelling and/or palmar and plantar erythema), bilateral nonsuppurative conjunctivitis, and unilateral cervical lymphadenopathy. Atypical KD refers to patients who have not met the full criteria and in whom atypical features may be present. We discuss a case of a 6-year-old male who presented to the Emergency Department with torticollis. A series of investigations for elevated inflammatory markers revealed dilated coronary artery aneurysms on echocardiogram, and thus he was diagnosed with atypical KD. His only other criteria were bilateral nonsuppurative conjunctivitis and a prior brief febrile illness. He was treated with high-dose intravenous immune globulin (IVIG) and low-dose aspirin. Low-molecular-weight heparin and atenolol were added due to the presence of giant aneurysms.